Peran Digital Marketing, Word Of Mouth dan Brand Awareness dalam Mempengaruhi Keputusan Siswa Bersekolah Di GIBS - Ahmadi Marta; Hairudinor; Marhusin (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2025)
Abstract: This research tries to analyze the role of Digital Marketing, Word of Mouth and Brand Awareness on students' decisions in choosing a school. The samples taken were 113 students at SMA Global Islamic Boarding School (GIBS) classes X and X1. By using a quantitative approach with Structural Equation Modeling (SEM) analysis, the data is then processed using the Smart PLS version 3 application. The research results state that Brand Awareness has a significant effect on choosing decisions. Digital Marketing has no significant effect on Brand Awareness. Digital Marketing has no significant effect on the decision to choose a school. Digital Marketing has a significant influence on WOM. WOM has a significant effect on Brand Awareness. WOM has a significant influence on choosing decisions. Digital Marketing has a significant indirect influence on the decision to choose a school mediated by WOM. Then Finally, Digital Marketing has a significant indirect influence on the Brand Awareness mediated by WOM